Problematika Penegakan Hukum Tindak Pidana Pencucian Uang - Rininta Rininta; Hartanto Hartanto (Universitas Medan Area, 2021)
Money laundering is a crime that always exists, and recently there have been massive cases in Indonesia, related technological and social advances are factors that cause money laundering crimes. Money laundering has continued to develop since the past until now the government is trying to follow up the law on money laundering, so it is important for us to discuss. Law No. 8/2010 The Prevention and Eradication of the Crime of Money Laundering is examined with a normative juridical approach in this study, with various breakthroughs, namely proof and fines. This category of crime is a transnational crime and a white-collar crime that has a destructive impact on the economy as well as the nation and state, so that efforts must be made in various ways to overcome it, namely by optimizing the duties and authorities of the PPATK, and cooperation between countries.